Effect of Sonographically Guided Cerebral Glioma Surgery on Survival Time - Wang, Jia; Liu, Xi; Ba, Yong Mei; Yang, Yi Lin; Gao, Guo Dong; Wang, Liang; Duan, Yun You (Journal of ultrasound in medicine, 2012)
Objectives We investigated the value of intraoperative sonography in improving the prevalence of total tumor resection and the survival time of patients who underwent resection of cerebral gliomas. Methods One hundred thirty‐seven patients who underwent sonographically guided surgery were followed for 6 to 60 months. In addition, 60 randomly selected patients (30 with low‐grade gliomas and 30 with high‐grade gliomas) who had surgery in our hospital without sonographic guidance served as the control group. Follow‐up included the survival time, and the difference in the survival time between the study and control groups was statistically analyzed. Results Total removal of the lesion was achieved in 77 cases (69%), and partial removal was achieved in 35 (31%). In the control low‐grade glioma group, 6‐month survival was 96.7%; 1‐year survival was 73.3%; and 2‐year survival was 53.3%. In the study low‐grade glioma group, survival rates at 6 months, 1 year, and 2 years were 98.0%, 96.1%, and 88.2%, respectively. In the control and study high‐grade glioma groups, survival rates at 6 months, 1 year, and 2 years were 83.3% and 93.4%, 43.3% and 59.2%, and 13.3% and 32.8%. When comparing survival at 6 months, 1 year, and 2 years between the control and study groups, there was no significant difference at 6 months (P > .05), but survival at 1 and 2 years was significantly different (P < .05). Conclusions Sonographically guided resection of cerebral gliomas helps the surgeon understand the relationship between the lesion and the surrounding structures. It is of value in improving the prevalence of total tumor resection and the patient's survival time.